Durabilitas Lapisan Asphalt Concrete-Wearing Course (AC-WC) Dengan Menggunakan Abu Terbang Sebagai Bahan Pengisi Di Lingkungan Air Gambut - Muhammad Akbar; Alfian Malik; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In the road pavement mixture, filler has a significant effect because it functions as a cavity filler. One of the filler that is commonly used is fly ash. Fly ash is a coal combustion waste that can be utilized and has a high silica content so as to improve the quality of the road pavement mixture. The purpose of this study is to determine the durability of the AC-WC layer using fly ash fillers in peat water environments. The proportion of fly ash used was 0%, 2%, 4%, 6% and 8%, each variation of fly ash was immersed for 0.5 hours, 24 hours, 48 hours, 72 hours, and 96 hours in peat water. The specification used follows the 2018 Bina Marga standard using the Marshall method. The results show that the AC-WC mixture submerged in peat water would experience a decrease in the value of stability and durability of the mixture. The highest stability value is 1308.08 kg at 0.5 hour immersion, while the lowest stability value at 96 hours immersion is 927.42 kg. However, the use of fly ash as filler will increase the stability and mixture values. The highest stability value for the AC-WC mixture is 1308.80 kg at 6% fly ash variation. This is caused by fly ash being able to maintain stability and durability when submerged in peat water. The optimum variation of fly ash filler which can be added to the AC-WC mixture is 6% of the total weight of the aggregate. This value is based on a high stability value compared to other variations of 1308.80 kg. As for the RSI value, the AC-WC mixture is able to withstand damage up to 48 hours which is equal to 90.07%Keywords: Fly ash, Filler, AC-WC, durability